2003
DOI: 10.2166/wst.2003.0179
|View full text |Cite
|
Sign up to set email alerts
|

Laser scanning detection of FISH-labelled Escherichia coli from water samples

Abstract: The development of rapid and accurate methods for the detection and quantification of bacteria without cultivation is of increasing importance for water monitoring. The aim of this study was to develop a solid phase cytometry detection method for DVC-FISH labelled Escherichia coli cells. In order to allow Stomatic detection with ChemScan RDI, the fluorescein-tyramide was combined with an oligonucleotide probe directly labelled with horseradish peroxidase to increase the fluorescence intensity. The method devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
3
3
0
1
Order By: Relevance
“…Our results are consistent with previous studies which demonstrated that FISH gives a too weak signal for SPC (24,34) and that CARD-FISH is a methodical improvement to increase the fluorescence signal (30). The choice of an appropriate amplification time during the CARD-FISH protocol is especially important for increasing the signal.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with previous studies which demonstrated that FISH gives a too weak signal for SPC (24,34) and that CARD-FISH is a methodical improvement to increase the fluorescence signal (30). The choice of an appropriate amplification time during the CARD-FISH protocol is especially important for increasing the signal.…”
Section: Discussionsupporting
confidence: 92%
“…This fact is an important advantage over flow cytometry and fluorescence microscopy, for which, in contrast to solid-phase cytometry, large volumes need to be concentrated for detection of rare events. Unfortunately, previous studies (24,34) have shown that the fluorescence signals of standard FISH-labeled microorganisms were too weak to be detected with solid-phase cytometry. Catalyzed reporter deposition-FISH (CARD-FISH) is one methodical improvement to increase the signal intensity of microorganisms (30,33,37).…”
mentioning
confidence: 98%
“…Although the PCR method is considered to be more sensitive than either FISH or the culture methods, more H. pylori ‐positive samples were obtained by the FISH technique than by culture or PCR analysis, confirming previous reports . PCR analysis allowed for the direct detection of H. pylori DNA in only three raw samples.…”
Section: Resultssupporting
confidence: 83%
“…12 The application of flow cytometry (FCM) provides a more rapid and reliable quantification than epifluorescence microscopy, ensuring accuracy and precision in enumeration. 13−15 However, previous studies have demonstrated that FISH gives a signal that is too weak for flow-cytometric measurements, 16,17 which greatly limits the utilization of FISH for identification of microbes with slow growth rates (e.g., anammox bacteria) or low ribosome contents. 18 Catalyzed reporter deposition (CARD)-FISH is a methodical improvement in fluorescence signal enhancement 19 that has been applied to the detection and quantification of microorganisms characterized by low ribosome contents or rather low abundance, such as marine microorganisms, biofilms, and benthic detritus.…”
Section: ■ Introductionmentioning
confidence: 99%